EmrA1 Membrane Fusion Protein of Francisella tularensis LVS is required for Resistance to Oxidative Stress, Intramacrophage Survival and Virulence in Mice - Ma, Zhuo (2014)
Francisella tularensis is a Category A Biodefense agent that causes a fatal human disease known as tularemia. The pathogenicity of F. tularensis depends on its ability to persist inside host immune cells primarily by resisting an attack from host-generated reactive oxygen and nitrogen species (ROS/RNS). Based on the ability of F. tularensis to resist high ROS/RNS levels, we have hypothesized that additional unknown factors act in conjunction with known antioxidant defenses to render ROS resistance. By screening a transposon insertion library of F. tularensis LVS in the presence of hydrogen peroxide, we have identified an oxidant sensitive mutant in putative EmrA1 (FTL_0687) secretion protein. The results demonstrate that the emrA1 mutant is highly sensitive to oxidants and several antimicrobial agents, and exhibits diminished intramacrophage growth that can be restored to wild type F. tularensis LVS levels either by transcomplementation, inhibition of ROS generation, or infection in NADPH oxidase deficient (gp91Phox(−/−)) macrophages. The emrA1 mutant is attenuated for virulence, which is restored by infection in gp91Phox(−/−) mice. Further, EmrA1 contributes to oxidative stress resistance by affecting secretion of Francisella antioxidant enzymes SodB and KatG. This study exposes unique links between transporter activity and the antioxidant defense mechanisms of F. tularensis.